Community Empowerment Strategy Through Local Wisdom By The Village Community Empowerment Service Using An Ecosystem Approach In The Era Of The Industrial Revolution In The Meepago Traditional Territory, Central Papua Province - Marinus Moy Yumai; Ismail Nurdin; Margaretha Rumbekwan (Jurnal Scientia, 2024)
The results of this research aim to raise the issue of the community empowerment strategy implemented by the Village Community Empowerment Service (DPMK) through the use of local wisdom in the Meepago traditional area in the context of the Industrial Revolution 4.0 era. The research method used is a qualitative research method to formulate ideal conditions for community empowerment through local wisdom with an ecosystem approach in the Meepago traditional area, Central Papua province. The researcher used two theories, namely the JunghoRoh theory (2018) and strategy analysis using ASOCA, which stands for (Ability.Strength,Opportunities, Culture and Agility). According to Suradinata (2014:18), ASOCA analysis adds elements of culture (culture) and agility (intelligence) as important elements in finding problem-solving strategies, decision making, and can be developed to follow changes, developments and needs. Based on the data and analysis described previously, it can be concluded that this research found that empowerment strategies based on local wisdom not only strengthen the cultural identity of the Meepago community but are also able to encourage innovation and technological adaptation that is relevant to local needs. In addition, collaboration between government, society and the private sector through an ecosystem approach produces effective synergies in achieving sustainable development goals.